Natinonal Education Policy Information System for EPRD Education Planning and Policy Research Division Ministry of Education, Malaysia / Tan Chim Tat - Tan, Chim Tat (2002)
National Education Policy Information System (NEPIS) is a web based system developed with the objective of implementing the information system on the Internet as a solution to publish education policy to the users in an effective manner. Overview of the proposed system is discussed in the beginning of this document followed by a review on current systems and development technologies. Then, the reader is introduced to system requirements and system design. Finally, the system design of NEPIS is presented to the reader. It consists of two modules. The administrator module enables administrator to maintain the database that stores related documents and access control to the database while the user module provides search, browse and view features to facilitate retrieving the intended documents and feedback capabilities for returning users' comment about the system. A mixture of waterfall, prototyping and incremental methodology is used to develop these two modules. It is hope that by combing three developments methodology can ease the development process and get the best result out of these methodologies. NEPIS is developed using Microsoft Visual lnterOev as the development environment for Active Server Page on Microsoft Windows NT 4.0 platform. Microsoft SOL Server 7 .o is used to create database and store information on education policy. The proposed system is expected to provide some basic features for retrieving related documents and to p1ovide room for future improvement.